Bacterial cell surfaces : methods and protocols - Delcour, Anne H. (methods and protocols, 2013)
This Methods in Molecular Biology(t) book gathers tools for studying protein structure and function and enzymatic activities, purifying and analyzing of macromolecules and their complexes and investigating regulatory mechanisms and cell biological processes